Economic factors in the future delivery of spinal healthcare - Rossi, Vincent J (World J Orthop, 2015)
The current trajectory of healthcare-related spending in the United States is unsustainable. Currently, the predominant form of reimbursement is the form of a fee-for-service system in which surgeons are reimbursed for each discrete unit of care provided. This system does factor the cost, quality, or outcomes of service provided. For the purposes of cost containment, the bundled episode reimbursement has gained popularity as a potential alternative to the current fee-for-service system. In the newer model, the spinal surgeon will become increasingly responsible for controlling costs. The bundled payment system will initially offer financial incentives to initiate a meaningful national transition from the fee-for-service model. The difficulty will be ensuring that the services of surgeons continue to be valued past this initiation period. However, greater financial responsibilities will be placed upon the individual surgeon in this new system. Over time, the evolving interests of hospital systems could result in the devaluation of the surgeons’ services. Significant cooperation on behalf of all involved healthcare providers will be necessary to ensure that quality of care does not suffer while efforts for cost containment continue.